COMMUNITY PHARMACISTS RECOMMENDATIONS ON SELF-MEDICATION FOR GASTROINTESTINAL PROBLEMS: A VIGNETTE CASE STUDY IN EAST SURABAYA - Djunaidy, Vania Denise; Parwitha, Ida Ayu Andri; Ferinandra Setyopratami, Angela Natasya (Journal Pharmaceutical Science and Application, 2025)
Background: Self-medication is a common approach to managing uncomplicated health issues, including gastrointestinal disorders. Community pharmacists are essential in facilitating successful self-medication by thoroughly evaluating patient information, offering rational suggestions, and delivering clear instructions regarding medication administration. Objective: This study aims to characterize pharmacists' abilities in gathering information on patient symptoms and providing appropriate treatment recommendations for self-medication cases of diarrhea and constipation. Methods: This study employed a cross-sectional methodology accompanied by descriptive analysis. Data was collected using two validated vignette case studies: one for measuring information-gathering competencies and another for assessing the correctness of therapy recommendations. Results: 35 pharmacists participated, most of whom had finished professional pharmacist education (88.6%) and had been practicing in pharmacies for 1 to 7 years (40%). The results showed that 66.0% of pharmacists demonstrated moderate information-gathering skills for diarrhea cases and a lower proportion for constipation cases (45.7%). Only 51.4% of pharmacists could provide correct recommendations for diarrhea and constipation cases. Conclusion: These findings highlight the importance of interventions to enhance pharmacists' roles in providing patients with appropriate, safe self-medication services. Keywords:  self-medication; community pharmacists; diarrhea; constipation